Learner Types and Their Preferences in Learning English - Masitowarni Siregar; Fahri Haswani (BIRCU, 2020)
The research was conducted to find out the most dominant learners’ types and to describe their preferences in learning English at the first semester in academic year 2018/2019English Education Study Program, Languages and Arts Faculty , Universitas Negeri Medan. The subject of the study was one class consisting 30 students. The collecting data in the research was by using learner types and preferences questionnaires and observing the learning process in the classroom. The result showed that there were some types of learners in this case. Concrete learner with their preferences are playing game, paying attention to thepictures, watching film is the most dominant one (40.00%). Preference of analytical learners relates to study grammar and English boo, it also relates to find the learners’ own problems (16.67%). Communicative learners (23.33%) with their preferences tend to listen to native speaker, to talk to friend in English and to watch English channel in you tube. The learners who are authority-oriented (20.00%) with their preferences are understanding the teacher’s explanation and writing everything in a notebook.